A Participatory Development Strategy for Sugar Palm Plantation Community - Kong-at, Chaiyan; Vongkamjan, Suphawan; Panyanuwat, Anurak; Gusolsatit, Thassanupan (Richtmann Publishing, 2012)
The objectives were 1) to create the development strategy for sugar palm plantation community, and 2) to experiment thedevelopment strategy for sugar palm plantation community in Keoychai Subdistrict, Chumseang District, Nakhon Sawan Province.Qualitative research and quantitative research approaches were used. The experiment group composed of 50 peoples that were dividedinto 10 peoples for each group and they were local scholars or knowledgeable peoples in the sugar palm, sugar palm owner, sugar palmproducers, suppliers of sugar palm product, community leaders and local leaders. Data collection and analysis were done withdocument, In-Depth interview, focus group discussion, observation and participatory action research. The analysis revealed that theimportant problem solving were the sugar palm plantation community at Keoychai District lacks of adaptation to suit with the prosperousperiod. The results of testing of system operation with the experimental group who were stakeholders, it was found that Unit 5: Toestablish a center of strategic development with the satisfaction of stakeholders at the highest level of 4.54 and satisfaction ofstakeholders with strategy development of overall average at the highest level of 4.51. The satisfaction of 60 visitors who came to visit,receive service and purchase the sugar palm product, the strategy of â€œwatching, tasting, shopping, and taking photographâ€ by setting 4sites for the visitors, it was found that shopping site with the satisfaction of visitors at the high level of 4.06 and overall averagesatisfaction of visitors at the high level of 3.97.